مورفومترية حوض وادي مركه سور في محافظة أربيل - عبد الستار العذاري أ.م.د. أحمد; عبد الحسين الربيعي حسين كاظم (Journal of College of Education, 2021)
The research aims to study the morphometric characteristics of the basin Mirga Sur Valley , that located in Irbil province in the north-east of mountainous region of Iraq ,with an area of (162.1 km2(.This research aims to identify the natural geographical in the basin that represent by: geological formations, climate, soil, natural vegetation, and the progress of geomorphological processes in the region, and the characteristics of the river network. The result shows that the effect of these factors vary in geomorphology and the characteristics of the basin, as the geological structure and its associated diversity of rocky, as in the Qmjoukh formation (resistant to erosion), the Onganh formation (average resistance to erosion) and the Tangroa formation (weak resistance to erosion),Which affects in response to weathering and erosion factors , as well as structural distortions suffered by the research area of the structures of sin, and breaks. This affects the response variance to weathering and erosion, as well as deformities structural experienced by the study area of the linear and breaks compositions. also the results show the spatial characteristics of river network (the length of basin 21.9 km, average width of the basin 7.4 km) and formal (roundness ratio 0.5 and the elongation ratio 0.9) topographic characteristics (Altdhars 67.4 m / km, weaving ratio pelvic 2.81) and morphometric characteristics of network aqueous drainage basin (bifurcation rate ratios of 4.94, 1.27 linear density, numerical density 0.94) .